Microstructural Evolution of Calcium Sulfoaluminate Cement during the Wet-Carbonation Process - Yangyang Zhang; Hang Yang; Qunli Zhang; Quan Qian; Chengwei Zhang; Kai Wu; Peiliang Shen (Buildings, 2024)
Calcium sulfoaluminate (CSA) cement, as a type of low-carbon cement, can contribute to further reduction in carbon emissions with carbonation technologies. However, the detailed microstructure development of CSA cement during the carbonation process has been rarely analyzed. In this paper, wet carbonation was applied to CSA cement to investigate the microstructure evolution of carbonation products and carbon absorption capacity of CSA cement by means of pH measurement, X-ray diffraction (XRD) measurement, thermogravimetric (TG) measurement, Fourier-transformed infrared spectroscopy (FT-IR) measurement and scanning electron microscope measurement. During the carbonation process, the formed ettringite product and the dicalcium silicate clinker were carbonated immediately to generate calcium carbonate crystals, silica gel and aluminum hydroxide (AH3) gel. With the trend of pH increasing first and notably decreasing later, the coupling interaction between the hydration and carbonation reactions of CSA cement was revealed. From the XRD and TG results, three types of calcium carbonate crystal forms (calcite, vaterite and aragonite) were detected, and the content of calcium carbonate increased with the increase in carbonation time. FT-IR analysis further confirmed the existence of calcium carbonate, silica gel and AH3 gel with their characteristic vibrations. Moreover, the microstructure of carbonation products with different morphologies was observed. The application of wet carbonation to CSA cement provides a more comprehensive insight to the carbonation mechanism of this low-carbon cement.